SURVEI SARANA DAN PRASARANA PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SEKOLAH LUAR BIASA NEGERI KENDAL DAN SEKOLAH LUAR BIASA ABC SWADAYA DI KABUPATEN KENDAL (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Research purposes to determine the availability of sports facilities and infrastructure on physical education and health in sport SLB Kendal. Types of research used in this study is a qualitative research method survei.Populasi used in this study is comprised two schools, namely SLB SLB ABC Domestic Non Kendal and Kendal. Methods of data collection using observation, documentation, and interviews. Analysis using descriptive analysis techniques percentage. Results of research in the School of Foreign Extraordinary Kendal produce availability sarpras by 389.9% 0.9% larger than ABC SLB "Swadaya" Kendal at 389%. Number of types of exercise equipment SLB Negeri Kendal 27 types of sports equipment more than 5 types of exercise equipment SLB ABC "Non" Kendal as many as 22 kinds of sports. The need to increase adaptive infrastructure penjas both quantitatively and qualitatively.